Engage me: Will residency program directors listen?. (August 2021) - Selvakumar, Sruthi; McKenney, Mark; Elkbuli, Adel
Highlights: The implementation of multi-level modifications, including but not limited to outreach initiatives and the development of a holistic application review approach, are potential strategies to improve diversity and inclusivity in general surgery residency recruitment. We encourage program directors to invest in trainees' success and implement human capital changes that produce sustinable and effective changes, and help in building the pipeline. Program directors are encouraged to work with their institutions to develop a holistic review approach through the following initiatives: recruitment of an inclusive and diverse interview selection committee, implementation of implicit bias training among all faculty and residents participating in the selection process, and promotion of structured interviews that focus on applicant characteristics that resonate with the program's mission statement.